Cytokine and Chemokine Levels in Coronavirus Disease 2019 Convalescent Plasma. (26th November 2020) - Bonny, Tania S; Patel, Eshan U; Zhu, Xianming; Bloch, Evan M; Grabowski, M Kate; Abraham, Alison G; Littlefield, Kirsten; Shrestha, Ruchee; Benner, Sarah E; Laeyendecker, Oliver; Shoham, Shmuel; Sullivan, David; et al.
Abstract: Background: The efficacy of coronavirus disease 2019 (COVID-19) convalescent plasma (CCP) is primarily ascribed as a source of neutralizing anti-severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) antibodies. However, the composition of other immune components in CCP and their potential roles remain largely unexplored. This study aimed to describe the composition and concentrations of plasma cytokines and chemokines in eligible CCP donors. Methods: A cross-sectional study was conducted among 20 prepandemic healthy blood donors without SARS-CoV-2 infection and 140 eligible CCP donors with confirmed SARS-CoV-2 infection. Electrochemiluminescence detection-based multiplexed sandwich immunoassays were used to quantify plasma cytokine and chemokine concentrations (n = 35 analytes). A SARS-CoV-2 microneutralization assay was also performed. Differences in the percentage of detection and distribution of cytokine and chemokine concentrations were examined by categorical groups using Fisher's exact and Wilcoxon rank-sum tests, respectively. Results: Among CCP donors (n = 140), the median time since molecular diagnosis of SARS-CoV-2 was 44 days (interquartile range = 38–50) and 9% (n = 12) were hospitalized due to COVID-19. Compared with healthy blood donor controls, CCP donors had significantly higher plasma levels of interferon (IFN)-γ, interleukin (IL)-10, IL-15, IL-21, and macrophage-inflammatory protein-1, but lower levels of IL-1RA, IL-8, IL-16, and vascular endothelial growth factor-A ( P  < .0014). The distributions of plasma levels of IL-8, IL-15, and IFN-inducible protein-10 were significantly higher among CCP donors with high (≥160) versus low (<40) anti-SARS-CoV-2 neutralizing antibody titers ( P  < .0014). The median levels of IL-6 were significantly higher among CCP donors who were hospitalized versus nonhospitalized ( P  < .0014). Conclusions: Heterogeneity in cytokine and chemokine composition of CCP suggests there is a different inflammatory state among the CCP donors compared with SARS-CoV-2 naive, healthy blood donors. Abstract : Compared to controls, COVID-19 convalescent plasma (CCP) had higher distributions of IFN-γ, IL-10, IL-15, IL-21, and MCP-1 but lower IL-1RA, IL-8, IL-16, and VEGF-A. Between CCP with low versus high neutralizing antibody titers, IL-8, IL-15 and IP-10 distributions varied significantly.